Psychological Distress on Mualaf - M. Yusuf Effendi; Dyah Astorini Wulandari (Proceedings Series on Social Sciences & Humanities, 2021)
Psychological distress is a harmful condition that can affect individuals directly or indirectly over time and affect physical health conditions and mental conditions. This study aims to determine the description of psychological distress in converts. This type of research is qualitative research with a phenomenological model and data collection methods carried out by in-depth interviews and documentation. The informants of this study were three people, one man was 59 years old and had converted to Islam for 36 years and two women, the first was 40 years old and had converted to Islam for 18 years, the second was 66 years old and had converted to Islam for 41 years. The results of this study indicate that the religious conversion experienced by the informant has a relationship with psychological distress, where the process follows the interpersonal and situational factors shared by the informant. The informant decides to convert to Islam. The interpersonal factors experienced by the informants occurred in the second stage of religious conversion, namely, the phase of unease. In this phase, religious teachings are believed to bring peace no longer or cause psychological distress to him. Informants make comparisons from the previous instructions to the teachings of Islam. The peak was the situational factor he experienced, namely the stage of religious conversion (mualaf) because the teachings in Islam are considered the right way and are more capable of bringing life satisfaction.